Divergent functions of the Arabidopsis mitochondrial SCO proteins: HCC1 is essential for COX activity while HCC2 is involved in the UV-B stress response - Iris eSteinebrunner; Uta eGey; Manuela eAndres; Lucila eGarcia; Daniel H Gonzalez (Frontiers in Plant Science, 2014)
The two related putative cytochrome c oxidase (COX) assembly factors HCC1 and HCC2 from Arabidopsis thaliana are Homologs of the yeast Copper Chaperones Sco1p and Sco2p. The hcc1 null mutation was previously shown to be embryo lethal while the disruption of the HCC2 gene function had no obvious effect on plant development, but increased the expression of stress-responsive genes. Both HCC1 and HCC2 contain a thioredoxin domain, but only HCC1 carries a Cu-binding motif also found in Sco1p and Sco2p. In order to investigate the physiological implications suggested by this difference, various hcc1 and hcc2 mutants were generated and analyzed. The lethality of the hcc1 knockout mutation was rescued by complementation with the HCC1 gene under the control of the embryo-specific promoter ABSCISIC ACID INSENSITIVE 3. However, the complemented seedlings did not grow into mature plants, underscoring the general importance of HCC1 for plant growth. The HCC2 homolog was shown to localize to mitochondria like HCC1, yet the function of HCC2 is evidently different, because two hcc2 knockout lines developed normally and exhibited only mild growth suppression compared with the wild type. However, hcc2 knockouts were more sensitive to UV-B treatment than the wild type. Complementation of the hcc2 knockout with HCC2 rescued the UV-B-sensitive phenotype. In agreement with this, exposure of wild-type plants to UV-B led to an increase of HCC2 transcripts. In order to corroborate a function of HCC1 and HCC2 in COX biogenesis, COX activity of hcc1 and hcc2 mutants was compared. While the loss of HCC2 function had no significant effect on COX activity, the disruption of one HCC1 gene copy was enough to suppress respiration by more than half compared with the wild type. Therefore, we conclude that HCC1 is essential for COX function, most likely by delivering Cu to the catalytic center. HCC2, on the other hand, seems to be involved directly or indirectly in UV-B-stress responses.